Health policy in the Polish health care system - Martyna Warchoł; Anna Kowalczyk; Mateusz Babula (Journal of Education, Health and Sport, 2019)
The main goal of health policy is to ensure the health security of society. There are many definitions of health policy. Health policy is one of the most important forms of public activity. Health policy programs include multi-annual programs established by the Council of Ministers. They implement the strategies adopted by the government - they concern important phenomena and problems that require decisions and actions at the level of the Council of Ministers. As part of social policy, it should be embedded in social and economic realities and be oriented on ensuring conditions favorable to maintaining the health of societies.